Incesto consentido entre irmãos: um outro olhar a partir da psicanálise - Gouveia, Michele dos Santos (2018)
The main objective of this research was to investigate the consented incest among siblings from another perspective, distanced from the perspective of sexual abuse. We inquire about the psychic and social implications for those who live the experience of the incestuous act (incestuous sexual act) without meaning it as violence. It is a theoretical research that makes an articulation between the art and the psychoanalysis of Freud and Lacan. For that, a bibliographical survey was carried out divided in three chapters and in a chapter one develops a reading of the French film Marguerite and Julien - A love forbidden (2017) to illustrate the discussion. Finally, this research found a shortage of Brazilian literature on consented incest, having found in some international authors a dialogue on the topic. In addition, it was possible to propose an extension of the subject of incest that can manifest in various ways, both from the point of view of the choice of incestuous object, and the way the subject deals with that relationship, being able to live it without meaning it as violence. The development of the research made possible to establish a difference between incest among siblings and structural incest, which includes the triad of the Oedipus complex, which consists of the relation of the subject to the paternal and maternal function. Thus, it was understood that the distinction of the type of incest, whether abusive or consensual, is fundamental for the clinical management and understanding of the implications that involve a type of sexual object choice that goes against the prevailing sexual morality